Scientific Approaches to Development of Medicinal Formulation Based on Biotechnological Substance - R. A. Abramovich; V. A. Bykov; I. A. Elagina; N. A. Papazona; A. N. Vorobyev (Антибиотики и Химиотерапия)
The study demonstrated possible design of a medicinal formulation in the form of suppositories comprising human recombinant interferon-α2 and dry aloe extract. The approaches to the development of the suppositories were technology - derived. No interaction between the active and auxiliary components was proved by solid state1H-NMR spectroscopy. The specific activity of the drug was investigated.